Meet the Challenge (African Knowledges and the History Publication since the 1970s)
Moderated and judged competition on scientific knowledge between students from Haywood Mission Institute vs. W. V. S. Tubman High School.
Keywords: Competition; Education; Scientific Knowledge; Quiz Show